Prolonged fibroblast growth factor 19 response in patients with primary sclerosing cholangitis after an oral chenodeoxycholic acid challenge - Zweers, Serge J; de Vries, Elisabeth M; Lenicek, Martin; Tolenaars, Dagmar; de Waart, D Rudi; Koelfat, Kiran V K; Groen, Albert K; Olde Damink, Steven W M; Beuers, Ulrich; Ponsioen, Cyriel; Jansen, Peter L M; Schaap, Frank G (Hepatology international, 2017)
BACKGROUND: Bile salts likely contribute to liver injury in patients with primary sclerosing cholangitis (PSC) and primary biliary cholangitis (PBC). Fibroblast growth factor 19 (FGF19) is a bile salt-induced enterokine with hepatoprotective potential as it suppresses de novo bile salt synthesis. Here, we evaluated the bile salt receptor FXR/FGF19 gut-liver axis in PSC and PBC patients. METHODS: Fasted patients with PSC (n = 12) and PBC (n = 10), and healthy controls (HC; n = 10) were orally challenged with the natural FXR agonist chenodeoxycholic acid (CDCA 15 mg/kg). Blood was sampled hourly until 8 h afterwards. Serum FGF19 and bile salt excursions were determined. Serum levels of 7α-hydroxy-4-cholesten-3-one (C4), reflecting bile salt synthesis, were measured as a biomarker of FGF19 response. RESULTS: Baseline serum FGF19 levels were comparable between groups, while fasted bile salt levels in PSC patients were elevated. Upon CDCA challenge, HC and PBC patients showed a serum FGF19 peak after 4 h followed by a decline. PSC patients showed a prolonged and elevated serum FGF19 response up to 8 h, combined with a sustained serum elevation of CDCA and other bile salts. In general, C4 levels declined following FGF19 elevation. In PSC patients with less favorable prognosis, baseline C4 levels were drastically suppressed and did not further decline. CONCLUSION: Following an oral CDCA challenge, PSC patients showed an impaired clearance of CDCA and a prolonged serum FGF19 response. FXR agonist therapy in PSC could cause prolonged exposure to elevated levels of FGF19, and we propose careful monitoring for detrimental side effects in patient studies.
Keywords: Liver; dospělí; Intestinal Mucosa; fibroblastové růstové faktory; Female; játra; Adult; ženské pohlaví; klinické protokoly; Chenodeoxycholic Acid; Fibroblast Growth Factors; sklerozující cholangitida; lidé; Primary sclerosing cholangitis; Farnesoid X receptor; Cholangitis, Sclerosing; studie případů a kontrol; purgativa; kyselina chenodeoxycholová; Male; Case-Control Studies; Aged; Fibroblast growth factor 19; aplikace orální; cholestenony; Cathartics; Chenodeoxycholic acid; lidé středního věku; senioři; mužské pohlaví; Administration, Oral; Cholestenones; Middle Aged; Clinical Protocols; střevní sliznice; Humans